HUBUNGAN ASUPAN ZAT GIZI, INDEKS MASSA TUBUH, DAN AKTIVITAS FISIK TERHADAP KADAR KOLESTEROL DARAH TOTAL PADA PASIEN PENYAKIT JANTUNG KORONER DI RSUD KOTA PRABUMULIH - Prata Sena, Nimas Agustine; Sa’pang, Mertien; Palupi, Khairizka Citra (Health Publica, 2020)
AbstractCoronary heart disease is heart disease caused by narrowing of the coronary arteries so that an interruption in blood flow to the heart muscle. The main risk factor is a risk factor total cholesterol abnormalities. There are several factors that can affect cholesterol levels, ie intake, body mass index, and physical activity. This study is to assess the relationship between intake of saturated fatty acids, PUFA, MUFA, fiber, niacin, vitamin C, magnesium, lycopene, physical activity and total blood cholesterol levels of patients with coronary heart disease in hospitals Prabumulih. This type of quantitative research with cross sectional study design with 40 respondents. Data taken in this study of the intake of saturated fatty acids, PUFA, MUFA, fiber, magnesium, lycopene, niacin, vitamin C, physical activity and total blood cholesterol levels by researchers. This study data analysis using correlation Pearson Product Moment Correlation. The result showed  There is a relationship between the intake of saturated fatty acids (p = 0.02), MUFA (p = 0.000), fiber (p = 0.016), physical activity (p = 0.000), BMI (p = 0.001) and total blood cholesterol levels. There was no relationship PUFA intake, magnesium, lycopene, niacin, and vitamin C with total blood cholesterol levels (p = 0.682; p = 0.568, p = 0.112, p = 0.062; p = 0.181).The intake of saturated fatty acids, MUFA, fiber, physical activity, BMI is a factor that affects the total blood cholesterol levels. Keywords: saturated fatty acids, fiber, magnesium, lycopene, vitamin